THE SYSTEMIC RISKS IDENTIFICATION AND CORRECTION IN THE PATIENT’S SANATORIUM REHABILITATION. FORMULATION OF THE PROBLEM - Sarkanych, O. V. (Medical Informatics and Engineering, 2017)
The methodology of assessing patients' condition in the general system of providing medical care is analyzed. A method for assessing the severity of a patient's condition based on the principles of personalized medicine is substantiated. The evaluation of the patient's stay in the sanatorium is considered as a macro-clinical model of the medical care system, consisting of two clusters — restoring health in a sanatorium and getting a proper rest.